2017
DOI: 10.2500/ajra.2017.31.4474
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal T-Cell Expression of Cytotoxic Mediators Granzyme B and Perforin is Reduced in Patients with Chronic Rhinosinusitis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In principle, GrB could also be delivered through this pathway. The CTLs release perforin and form pores on the surface of the target cell membrane, allowing direct diffusion of GrB into the cytoplasm of the cell thus helping its escape from endosome and lysosome degradation (Scheme 1a) 29-30. Consequently, abundant apoptosis pathways are activated, including caspase and BH3 interacting domain death (BID) agonist, and induce cell death (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In principle, GrB could also be delivered through this pathway. The CTLs release perforin and form pores on the surface of the target cell membrane, allowing direct diffusion of GrB into the cytoplasm of the cell thus helping its escape from endosome and lysosome degradation (Scheme 1a) 29-30. Consequently, abundant apoptosis pathways are activated, including caspase and BH3 interacting domain death (BID) agonist, and induce cell death (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Defective cytotoxic T-cell function has similarly also been implicated in the dysregulated immune response seen in CRS. 3 A novel study by Smith et al , 4 also published in this issue, set out to explore the mechanism behind this. In their study of patients with CRS with and without polyps, the investigators observed a decrease in the local production of the important cytotoxic T-cell mediators, granzyme B, and perforin, despite an increase in absolute cytotoxic T-cell numbers in the tissue of patients with CRS.…”
mentioning
confidence: 99%
“…In their study of patients with CRS with and without polyps, the investigators observed a decrease in the local production of the important cytotoxic T-cell mediators, granzyme B, and perforin, despite an increase in absolute cytotoxic T-cell numbers in the tissue of patients with CRS. 4 They postulated that it is possible that this deficiency may affect antiviral immunity and predispose patients with CRS to an exaggerated inflammatory response after a viral insult. 4…”
mentioning
confidence: 99%
See 2 more Smart Citations